Hubungan Pengetahuan dan Sikap Orang Tua Terhadap Tindakan Pencegahan Demam Thypoid Pada Anak - Maharani Desthia Putri; Sri Wahyuni; Petronela Mamentu (STIKES Columbia Asia Medan, 2023)
Typhoid fever is a type of infection caused by Salmonella Enterica bacteria, especially Salmonella Typhi derivatives. The purpose of this study was to determine whether there is a relationship between knowledge and attitudes of parents towards typhoid fever prevention measures in children in the dahlia room of Robert Wolter Mongisidi Kindergarten Hospital in Manado City. The study was conducted using analytical descriptive research methods that are cross sectional. The sample was taken based on the number of subjekts as many as 30 people using random sampling, data collection was carried out by giving questionnaires. Furthermore, the data that has been collected is processed using the help of the SPSS program computer to analyze the chi-square statistical test with a meaning level (α) of 0.05. The results showed that the most sex obtained in this study was 20 female subjekts (66.7%). The conclusion in this study is that there is a relationship between knowledge and attitudes of parents towards typhoid fever prevention measures in children p = 0.000. This p value is smaller than α = 0.05, there is a relationship between knowledge and parents' attitudes towards preventive measures against typhoid fever in children. The conclusion in this study is that there is a relationship between knowledge and attitudes of parents towards typhoid fever prevention measures in children p = 0.000. This p value is smaller than α = 0.05, there is a relationship between knowledge and parents' attitudes towards preventive measures against typhoid fever in children.